Korelasi Minat Belajar Dengan Hasil Belajar Mata Pelajaran Seni Budaya Dan Prakarya (SBdP) Siswa Kelas IV SD Setia Budi Sungailiat - Eka, Indah Eka Safitri; Asyraf Suryadin; Hevitria (Universitas Muhammadiyah Bangka Belitung, 2024)
The purpose of this study was to determine the correlation between learning interest and learning outcomes in the subject of Cultural Arts and Crafts (SBdP) for Class IV SD Setia Budi Sungailiat. The background of the problem occurs when students' interest in participating in the learning process requires guidance in learning so that students have an interest in learning. Therefore, learning is needed that can attract students' interest in learning, especially in learning Arts and Crafts (SBdP). The correlational research method uses a quantitative approach, so this research uses a saturated sampling technique using the entire population as a sample, namely all class IV students at Setia Budi Sungailiat Elementary School, totaling 22 students, namely by distributing questionnaires and questions. This researcher used SPSS 23. It is proven from the results of the correlation analysis between interest in learning and students' SBdP learning outcomes that the correlation index value is 0.790 > 0.423, the rcount value is greater than the rtable, which means it is in a position between 0.60-0.799, which means it is very strong, so the hypothesis in this study is accepted. namely, there is a positive correlation between interest in learning and learning outcomes in the Arts, Culture and Crafts (SBdP) subjects of class IV SD Setia Budi Sungailiat